Direct Synthesis of Multiplexed Metal‐Nanowire‐Based Devices by Using Carbon Nanotubes as Vector Templates. (11th June 2019) - Clément, Pierrick; Xu, Xinzhao; Stoppiello, Craig T.; Rance, Graham A.; Attanzio, Antonio; O'Shea, James N.; Temperton, Robert H.; Khlobystov, Andrei N.; Lovelock, Kevin R. J.; Seymour, Jake M.; Fogarty, Richard M.; Baker, Alastair; et al.
Abstract: We present the synthesis of metal nanowires in a multiplexed device configuration using single‐walled carbon nanotubes (SWNTs) as nanoscale vector templates. The SWNT templates control the dimensionality of the wires, allowing precise control of their size, shape, and orientation; moreover, a solution‐processable approach enables their linear deposition between specific electrode pairs in electronic devices. Electrical characterization demonstrated the successful fabrication of metal nanowire electronic devices, while multiscale characterization of the different fabrication steps revealed details of the structure and charge transfer between the material encapsulated and the carbon nanotube. Overall the strategy presented allows facile, low‐cost, and direct synthesis of multiplexed metal nanowire devices for nanoelectronic applications. Abstract : Auf dem rechten Weg halten : Metall‐ und Metalllegierungs‐Nanodrähte wurden durch die Verwendung von Kohlenstoff‐Nanoröhren als nanoskalige Vektorvorlagen gebildet, die eine präzise Steuerung von Größe, Form und Ausrichtung der Nanodrähte ermöglichten. Die Verwendung einer lösungsverarbeitbaren Methodik erlaubte die Herstellung elektronischer Multiplex‐Baugruppen auf demselben Chip (siehe Bild).